2018
DOI: 10.3847/1538-4357/aacd0e
|View full text |Cite
|
Sign up to set email alerts
|

A Deeper Look at the New Milky Way Satellites: Sagittarius II, Reticulum II, Phoenix II, and Tucana III

Abstract: We present deep Magellan/Megacam stellar photometry of four recently discovered faint Milky Way satellites: Sagittarius II (Sgr II), Reticulum II (Ret II), Phoenix II (Phe II), and Tucana III (Tuc III). Our photometry reaches ∼2-3 magnitudes deeper than the discovery data, allowing us to revisit the properties of these new objects (e.g., distance, structural properties, luminosity measurements, and signs of tidal disturbance). The satellite color-magnitude diagrams show that they are all old (∼13.5 Gyr) and me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 90 publications
6
72
0
Order By: Relevance
“…However, this does not mean that Sgr II cannot be a GC. There are GCs with Oo II characteristics similar to Sgr II in the inner halo (Clement et al 2001), andMutlu-Pakdil et al (2018) has further shown that its structural parameters are more consistent with extended GCs. Spectroscopic studies are eventually required to ascertain whether it is a galaxy or a star cluster, by investigating velocity and metallicity dispersions of the system and/or a possible presence of Na-O or Mg-Al anti-correlations shown only in GCs.…”
Section: Rr Lyrae Stars In the Field Of Sgr IImentioning
confidence: 91%
“…However, this does not mean that Sgr II cannot be a GC. There are GCs with Oo II characteristics similar to Sgr II in the inner halo (Clement et al 2001), andMutlu-Pakdil et al (2018) has further shown that its structural parameters are more consistent with extended GCs. Spectroscopic studies are eventually required to ascertain whether it is a galaxy or a star cluster, by investigating velocity and metallicity dispersions of the system and/or a possible presence of Na-O or Mg-Al anti-correlations shown only in GCs.…”
Section: Rr Lyrae Stars In the Field Of Sgr IImentioning
confidence: 91%
“…We determine the distance modulus of Leo V by counting the number of stars consistent with the M92 fiducial, as described in Mutlu-Pakdil et al (2018, see also Walsh et al 2008. We assume a distance modulus of m − M = 14.62 mag for M92 as in Brown et al (2014), taking the mean of measurements from Paust et al (2007, 14.60 ± 0.09 mag), Del Principe et al (2005,14.62 ± 0.1 mag), and Sollima et al (2006, 14.65 ± 0.1 mag).…”
Section: Distance and Color-magnitude Diagrammentioning
confidence: 99%
“…Their close proximity provides the possibility of detailed comparison between their observed properties and predictions from the concordance cosmology. Well-known discrepancies include the 'missing satellite' problem, where orders of magnitude more substructures are identified in the ΛCDM simulations than the number of observed satellite galaxies (Kauffmann et al 1993;Moore et al 1999;Klypin et al 1999;Mutlu-Pakdil et al 2018;Newton et al 2018), the 'too-bigto-fail' problem, that is, the most luminous observed satellites do not seem to live in the most massive dark subhalos expected from cosmological simulations, which however are 'too big to fail' at forming stars (Strigari et al 2010;Boylan-Kolchin et al 2011), the 'core-cusp' problem, where halos are less cuspy than the ΛCDM predictions (Simon et al 2005;Navarro et al 2010), and the 'planes of satellites' problem, where the observed satellite galaxies are distributed on a much thinner plane (Lynden-Bell 1982;Metz et al 2009;Pawlowski et al 2012;Ibata et al 2013) than substructures predicted by the ΛCDM model. Some of these discrepancies can be alleviated by reducing the expected host halo mass, for example, having fewer (massive) substructures in less-massive halos so that both the 'missing-satellite' problem and the 'too-big-tofail' problem could be less severe (Wang et al 2012;Cautun et al 2014a).…”
Section: Introductionmentioning
confidence: 99%